PERILAKU PROFESIONAL GURU PROGRESIF - Asmuri Darma (POTENSIA: Jurnal Kependidikan Islam, 2017)
Teachers play a leading role and occupy a very crucial position in the world of education, especially education organized formally in both schools and madrasah. Therefore, the constitutional existence of teachers has been regulated in Law no. 14 of 2005 on teachers and lecturers. The law requires a number of teacher competencies as professional educators. Although formally the teacher is regarded as a professional educator, but in practice in the field various types and behavioral models presented by the teacher in realizing the duties and responsibilities of his profession as a teacher is mainly reflected in the learning activities in the classroom. There are behavioral behavior of teachers who are stagnant even tend to decline and there is also the behavior of teachers who experience improvement and progress. The latter is what is referred to as progressive professional behavior.